Human Skin Cancers - Pathways, Mechanisms, Targets and Treatments 2018
DOI: 10.5772/intechopen.70879
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Mechanisms and Biomarkers of Skin Photocarcinogenesis

Abstract: Skin cancer is the most commonly diagnosed malignancy in the United States and worldwide. While melanoma is the deadliest form of skin cancer, non-melanoma skin cancers, which include basal cell carcinoma and squamous cell carcinoma, are responsible for significant morbidity in millions of Americans each year. While numerous attempts have been made to reduce skin cancer risk factors related to ultraviolet radiation exposure, skin cancer incidence continues to rise. Improved understanding of the molecular pathw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 142 publications
0
12
0
Order By: Relevance
“…UV-B rays directly induce DNA lesions (misbonding of two pyrimidines, either thymine or cytosine, within the same DNA strand), because the wavelength of this specific radiation corresponds to the absorption spectrum of the genetic material. As such, UV-B photons are directly absorbed and lead to formation of cyclobutane pyrimidine dimers and pyrimidine 6-4 pyrimidone photoproducts, which left unrepaired become mutagenic [ 5 , 19 ]. In contrast to UV-B, the exact role of UV-A in cutaneous carcinogenesis is not clearly understood.…”
Section: Etiology Prevention and Early Diagnosis Of Cutaneous Sccmentioning
confidence: 99%
See 3 more Smart Citations
“…UV-B rays directly induce DNA lesions (misbonding of two pyrimidines, either thymine or cytosine, within the same DNA strand), because the wavelength of this specific radiation corresponds to the absorption spectrum of the genetic material. As such, UV-B photons are directly absorbed and lead to formation of cyclobutane pyrimidine dimers and pyrimidine 6-4 pyrimidone photoproducts, which left unrepaired become mutagenic [ 5 , 19 ]. In contrast to UV-B, the exact role of UV-A in cutaneous carcinogenesis is not clearly understood.…”
Section: Etiology Prevention and Early Diagnosis Of Cutaneous Sccmentioning
confidence: 99%
“…Epidemiologic studies also seem to support these harmful effects, and it has been reported that a single indoor tanning session, during which UV-A radiation emission is substantially higher than from natural sun [ 21 ], can increase the risk of developing cSCC by 67% [ 22 ]. In light of these findings, alternative pathways that lead to skin carcinogenesis are currently being searched for, to understand the mechanisms behind UV-A induced mutations [ 5 ].…”
Section: Etiology Prevention and Early Diagnosis Of Cutaneous Sccmentioning
confidence: 99%
See 2 more Smart Citations
“…Exposure to ultraviolet (UV) radiation induces the proliferation of melanocytes and the synthesis of melanin, the photoprotective pigment that is distributed to neighbouring keratinocytes via large specific vesicles termed melanosomes. Prolonged and intense exposure to UV is thought to be the main factor that determines melanomagenesis, as UV radiations can trigger oxidative stress and induce point mutations haphazardly across the genome, which can lead to loss of cell cycle control and apoptosis escape [ 4 , 5 ]. Extensive data from The Cancer Genome Atlas (TCGA) project partly defined the complex genetic landscape of melanoma, disclosing the high occurrence of somatic mutations and the prevalent activation of the mitogen-activated protein kinase (MAPK) pathway [ 6 ].…”
Section: Introductionmentioning
confidence: 99%